High-accuracy 4D particle trackers with resistive silicon detectors (AC-LGADs). (1st March 2022) - Arcidiacono, R.; Cartiglia, N.; Ferrero, M.; Mandurrino, M.; Menzio, L.; Siviero, F.; Sola, V.; Tornago, M.
Abstract: Future particle trackers will have to measure concurrently position and time with unprecedented accuracy, aiming at ∼5 μm and a few 10s ps resolution respectively. A promising good candidate for such a task are the resistive AC-LGADs, solid state silicon sensors of novel design, characterized by an internal moderate gain and an AC-coupled resistive read-out to achieve signal sharing among pads. The sensor design leads to a drastic reduction in the number of read-out channels, has an intrinsic 100% fill factor, and adapts easily to any read-out geometry. This report describes the design challenges, the signal formation and recent test results obtained with the first prototypes. A part is also dedicated to the reconstruction techniques that exploit the distributed nature of the signal, including machine learning. An outlook to a future development for optimized read-out electrodes and electronics is also presented.